Understanding vision: students’ use of light and optics resources - Jones, Dyan L.; Zollman, Dean A. (My University, 2014)
We present a qualitative study designed to examine how students construct an understanding of the human eye and vision from their knowledge of light and optics. As would be expected, vast differences are shown to exist between pre- and post-instruction students in terms of not only resource use, but also willingness to transfer their existing knowledge. However, we have found that appropriate scaffolding can facilitate resource activation and guide students to construct an understanding of vision and vision defects.
Keywords: Physics education; Optics; Quantum optics; Light and color detection